2020
DOI: 10.1007/s40121-019-00278-1
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Evaluation of Vancomycin-Associated Acute Kidney Injury in Hospitalized Patients with Acute Bacterial Skin and Skin Structure Infections

Abstract: Background: We sought to determine the realworld incidence of and risk factors for vancomycin-associated acute kidney injury (V-AKI) in hospitalized adults with acute bacterial skin and skin structure infections (ABSSSI). Methods: Retrospective, observational, cohort study at ten U.S. medical centers between 2015 and 2019. Hospitalized patients treated with vancomycin (C 72 h) for ABSSSI and C one baseline AKI risk factor were eligible. Patients with end-stage kidney disease, on renal replacement therapy or AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Vancomycin is a glycopeptide antibiotic used for treatment of methicillin-resistant Staphylococcus aureus infections in critically ill patients. Nephrotoxicity is a serious adverse event impacting 10–20% of treated patients and is associated with increased hospital length of stay, 30-day hospital readmission rates and all-cause 30-day mortality [ 1 ]. Vancomycin associated acute kidney injury (V-AKI) is dose-related and with an onset of 4–17 days therapy initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin is a glycopeptide antibiotic used for treatment of methicillin-resistant Staphylococcus aureus infections in critically ill patients. Nephrotoxicity is a serious adverse event impacting 10–20% of treated patients and is associated with increased hospital length of stay, 30-day hospital readmission rates and all-cause 30-day mortality [ 1 ]. Vancomycin associated acute kidney injury (V-AKI) is dose-related and with an onset of 4–17 days therapy initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotoxicity has been reported to contribute to approximately 8%–40% of all cases of acute renal injury. Since its introduction, vancomycin, a glycopeptide antibiotic often used as the last line of defense against drug resistant gram-positive bacteria, has been associated with acute renal injury [ 1 , 2 ]. Vancomycin is commonly used to treat hospital-acquired methicillin-resistant Staphylococcus aureus (MRSA) infections [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…infections [1]. Due to treatment failures, clinicians have been reported to be using higher doses of vancomycin [3].…”
mentioning
confidence: 99%
“…Vancomycin is often used as a irst line empiric therapy for many moderate-to-severe gram-positive infections and has been associated with AKI [4]. Given the widespread use of vancomycin, there are reports of VA-AKI ranging between 5% to 40% [2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that vancomycin could be both nephrotoxic and ototoxic [1]. Despite improvements in the puri ication process, literature suggests that vancomycin is still associated with 5% -40% increased incidence of acute kidney injury (AKI) [2][3][4][5][6]. A recent systematic review and meta-analysis suggested that use of vancomycin has a relative risk of 2.45 for development of AKI [7].…”
Section: Introductionmentioning
confidence: 99%